Effects of groundwater flow on the stability of an underground rock cavern - Natarajan Saravanan (2008)
In the present study, a stability of an underground cavern due to ground water flow was studied numerically using the distinct element method. The study incorporated the effects of joint geometry and their degree of interconnectivity, fault zones under static and fluctuating groundwater tables.